2017
DOI: 10.1088/1361-648x/aa80b3
|View full text |Cite
|
Sign up to set email alerts
|

Human-brain ferritin studied by muon spin rotation: a pilot study

Abstract: Muon spin rotation is employed to investigate the spin dynamics of ferritin proteins isolated from the brain of an Alzheimer's disease (AD) patient and of a healthy control, using a sample of horse-spleen ferritin as a reference. A model based on the Néel theory of superparamagnetism is developed in order to interpret the spin relaxation rate of the muons stopped by the core of the protein. Using this model, our preliminary observations show that ferritins from the healthy control are filled with a mineral com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…In contrast, the core of pathological ferritin consists primarily of cubic structures, such as magnetite and wustite, and to a lesser extent ferrihydrite, but with no hematite. These conclusions have been confirmed in a recent study [ 25 ], where muon spin rotation was utilized to demonstrate that ferritin particles have a crystalline phase with large magnetocrystalline anisotropy that is compatible with magnetite or maghemite. The altered composition of the ferritin’s mineral core could be associated with pathology.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast, the core of pathological ferritin consists primarily of cubic structures, such as magnetite and wustite, and to a lesser extent ferrihydrite, but with no hematite. These conclusions have been confirmed in a recent study [ 25 ], where muon spin rotation was utilized to demonstrate that ferritin particles have a crystalline phase with large magnetocrystalline anisotropy that is compatible with magnetite or maghemite. The altered composition of the ferritin’s mineral core could be associated with pathology.…”
Section: Introductionsupporting
confidence: 52%
“…As previously described, the mineral core of physiological ferritin consists of ferrihydrite, while the mineral core of ferritin associated with pathology consists of magnetite [ 24 , 25 ]. The size of the magnetite nanocrystals ranges from 10 to 70 nm [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both scaling to higher energies and cooling of positrons using this mechanism is yet unexplored. Beamdriven plasma acceleration of positrons [27,28] although compact by itself, depends on kilometer-scale GeV RF accelerators. Additionally, obtaining an appropriately spaced drive-witness bunch pair for beam-plasma acceleration methods is technologically di cult.…”
Section: College Of Engineering and Applied Science University Of Comentioning
confidence: 99%
“…work which uses sheath fields driven by kilo-J lasers in metal targets has obtained quasi-mono 10 MeV positrons [26] although with inherently peratures. Both scaling to higher energies and positrons using this mechanism is yet unexplore driven plasma acceleration of positrons [27,28] compact by itself, depends on kilometer-scale accelerators. Additionally, obtaining an app spaced drive-witness bunch pair for beam-plas eration methods is technologically di cult.…”
Section: College Of Engineering and Applied Science University Of Comentioning
confidence: 99%
“…It has been revealed that muon spin rotation spectroscopy is effective in detecting dissolved oxygen in blood and can be applied to medical treatments for hypoxia [20]. Recently, in a pilot study concerning Alzheimer's disease, the muon spin spectroscopy was used to analyze human-brain ferritin which is an iron storage protein [21]. On the basis of muon spin relaxation spectra on ferritin [22], it was discussed that minerals contained in ferritins from the healthy control and those of the Alzheimer's disease patients were different.…”
Section: Muon Spin Spectroscopic Approach To Monitoring Functions Of mentioning
confidence: 99%